Rekomendasi Peningkatan Kualitas Pelayanan di Terminal XYZ dengan Menggunakan Metode Servqual dan PGCV - Kamil, Muhammad Taufiq; Wijayanto, Dedi; Djanggu, Noveicalistus H (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Terminal XYZ is a terminal located in Kubu Raya Regency, West Kalimantan. Based on historical data from the Kubu Raya Central Bureau of Statistics (BPS), there has been a decline in the number of passengers from 2022 to 2024, particularly on intercity routes within the province (AKDP). In addition, there have been several complaints regarding poorly maintained facilities, such as the condition of the toilets, lighting, waiting area, and others. This study aims to assess passenger satisfaction with the services at Terminal XYZ and to provide recommendations for improving service quality using the Service Quality (SERVQUAL) and Potential Gain Customer Value (PGCV) methods. The results of the study indicate that out of 21 attributes, there are three attributes with the highest potential for increasing satisfaction: clean and odor-free toilets with a PGCV value of 8.705, adequate lighting conditions with a PGCV value of 7.803, and the availability of official, safe, and reliable partner taxi services with a PGCV value of 7.188.